Attenuation of intestinal ischemia-reperfusion-injury by anesthetics: a potentially protective effect of anesthetic management in experimental studies - Huang, Zhan; Bai, Yiping; Chen, Ying; Chen, Ye; Jiang, Yuan; Zhou, Jun (Frontiers in Pharmacology, 2024)
Intestinal ischemia-reperfusion injury (IRI) is a potentially severe clinical syndrome after major surgical procedures. In addition to causing intestinal mucosa injury, intestinal IRI further damages distant organs, causing the severity of the condition in patients. So far, effective therapy for intestinal IRI is still absent, and the survival rate of the patients is low. Previous experimental studies have shown that some anesthetics can alleviate intestinal IRI and protect organs while exerting their pharmacological effects, indicating that reasonable perioperative anesthesia management may provide potential benefits for patients to avoid intestinal IRI. These meaningful findings drive scholars to investigate the mechanism of anesthetics in treating intestinal IRI in-depth to discuss the possible new clinical uses. In the present mini-review, we will introduce the protective effects of different anesthetics in intestinal IRI to help us enrich our knowledge in this area.